About the Contributors - ‎, — (The Archive; Vol 2 No 1–2 (2021): Regular Issue Vol. 2, Nos. 1–2, 2023)
Jhony C. Azada is School Principal 1 of Uguis Integrated School, Schools Division of Ilocos Norte (SDO Ilocos Norte), an IPEd implementing school of the Itneg Inlaud community. He was awarded as Outstanding School Head of the SDO Ilocos Norte in 2019 and by Instabright International in 2021. He is also an alumnus of the International Leaders on Education Program sponsored by Fulbright Philippines at Arizona State University, USA in 2018. He is a writer and contributor to the Region 1 IPED Framework and the Four Minima of the Itneg Inlaud language. He is core team member of the Itneg Inlaud Language and Culture Documentation Project. Nick B. Bringas is the Head Teacher of Pila Elementary School in Cabugao, Schools Division of Ilocos Sur (SDO Ilocos Sur). He was awarded as Most Outstanding School Head of SDO Ilocos Sur in 2022. He was a writer and contributor to the Region 1 IPED Framework and the IPEd Curriculum Framework of SDO Ilocos Sur. He also serves as writer, evaluator, consultant, and language editor of LPs, LMs, and SLMs of SDO Ilocos Sur IPEd Programs. Further, Nick sits as Chairperson of the IPEd Coordinators of SDO Ilocos Sur. He is also one of the core team members of the Itneg Inlaud Language and Culture Documentation Project. Honeylet Dumoran is a graduate student of the UP Department of Linguistics. Under the PhD program, she has done grammar work on Mindanao languages: Salug-Subanen, Kamayo (Mandaya), and Talaandig (Binukid). Her dissertation work is on the Bilic languages (Tboli, Blaan, Teduray, and Klata). Honeylet has a master’s degree in English Language Studies. She is a member of the faculty of the Department of English of MSU-Iligan Institute of Technology in Mindanao. Maria Kristina Gallego is a PhD candidate at the School of Culture, History and Language, College of Asia and the Pacific, at the Australian National University. She is also an Assistant Professor at the Department of Linguistics, University of the Philippines Diliman. Her current research project explores the contact situation between Ibatan and Ilokano on the island of Babuyan Claro in the Philippines. Ryn Jean V. Gonzales works with SIL Philippines in Language Assessment and Documentation, Community-Based Language and Identity Development (CBLID), Literacy and Education, and Participatory Methods training. Since 2016, she has also been involved as a consultant-facilitator for Regional and Division level Indigenous Peoples Education (IPED) programs, particularly in the development of the Four Minima for Mother Tongue-Based Multilingual Education program implementation. Rynj, as she is fondly called by her peers, leads the Itneg Inlaud Language and Culture Documentation in the provinces of Ilocos Sur, Ilocos Norte, and Abra. She is also working on a grammatical description of Itneg Inlaud for her PhD dissertation with the Department of Linguistics, University of the Philippines Diliman. Jesus Federico C. Hernandez is an Associate Professor at the Department of Linguistics at the University of the Philippines in Diliman. He advocates decolonization of the practice of linguistics in the Philippines and integration of linguistic rights within the social justice framework. Marites F. Remos is Teacher III at Naguilian Elementary School, Nueva Era, Ilocos Norte. She has been involved as a writer and contributor to the Region 1 IPED Framework and the Four Minima for Mother Tongue-Based Multilingual Education (MTBMLE) implementation in Itneg Inlaud. She is also one of the core team members of the Itneg Inlaud Language and Culture Documentation Project. Michael Wilson Rosero obtained his Bachelor of Arts in Linguistics from the University of the Philippines Diliman in 2011, where he also worked as a part-time lecturer in the Department of Linguistics at UP Diliman (2013–2014). He was involved in reform initiatives in teacher quality, such as the development of the Philippine Professional Standards for Teachers (PPST), the alignment of the Department of Education’s (DepEd) human resource systems with PPST, the strengthening of the Teacher Education Council (TEC), and transformation of the National Educators Academy of the Philippines (NEAP). He obtained his Master of Education in Professional Development of Teachers, focusing on the School Reform Management program from the Department of Professional Development of Teachers, University of Fukui, Japan. He advocates for the advancement of multilingual and culturally relevant education in the Philippines and has been part of various research projects in social sciences, engineering, speech-language pathology, medical translation, and occupational therapy. Ava A. Villareal finished her MA in Linguistics from UP Diliman in 2021. She is currently enrolled in the PhD program of the department. She is the chairperson of the Surigaonon Studies Center, an advocacy group focusing on language documentation and promotion of Surigaonon and other languages in the area. Her research interests include Surigaonon grammar, structural linguistics, South Bisayan linguistics, South Bisayan language and cultural studies, and indigenous language and cultural studies.